Synthesis of linear multi‐beam arrays through hierarchical almost difference set‐based interleaving. Issue 10 (1st July 2014) - Oliveri, Giacomo; Viani, Federico; Massa, Andrea
Abstract : The study presents an innovative 'almost difference set (ADS)' ‐ based analytical approach for the design of fully interleaved arrays supporting Q > 2 independent functions on a shared aperture. Such a hierarchical subarraying methodology allows one to interweave, on the same lattice, Q = 2 P non‐overlapped arrangements with beam properties a‐priori predictable from the descriptive parameters of the chosen ADSs. A general formulation for the pattern analysis of subarray layouts is derived and successively employed to assess features and potentialities of the multi‐level 'ADS' interleaved scheme. A set of representative numerical results, concerned with different apertures, balancing factors and number of interleaved functions, is presented to give some indications on the effectiveness, the efficiency and the reliability of the proposed approach.